(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
The Moldovan parliamentary elections of 28 September 2025 between European aspirations and democratic weaknesses The paper examines the Moldovan parliamentary elections of 28 September 2025, highlighting their geopolitical importance and the democratic backsliding that marked the process. The confirmation of the pro-European PAS party took place in a context shaped by external interference, legislative reforms, and other measures that limited political pluralism, raising concerns about a gradual erosion of democratic safeguards.